Respiratory syncytial virus is present in the neonatal intensive care unit - Homaira, N.; Sheils, J.; Stelzer-Braid, S.; Lui, K.; Oie, J.; Snelling, Thomas; Jaffe, A.; Rawlinson, W. (WILEY-LISS, 2016)
© 2016 Wiley Periodicals, Inc. Nosocomial transmission of respiratory syncytial virus (RSV) occurs in children within the neonatal intensive care unit (NICU). During peak community RSV transmission, three swabs were collected from the nose, hand and personal clothing of visitors and health care workers (HCW) in NICU once every week for eight weeks. Nasal swabs were collected from every third neonate and from any neonate clinically suspected of having a respiratory infection. Environmental sampling of high touch areas was done once during the study period. All swabs were tested for RSV using real time RT-PCR. There were 173 (519 total) and 109 (327 total) swabs, each of nose, hand and dress from 84 HCWs and 80 visitors respectively and 81 nasal swabs from 55 neonates collected. Thirty five environmental swabs from surfaces of the beds, side tables, counter tops, chairs, tables and computers were collected. Overall 1% of nasal swabs from each of HCWs, visitors and neonates, 4% of dress specimens from visitors and 9% of environmental swabs were positive for RSV-RNA. The results suggest that though the risk for RSV in the NICU remains low, personnel clothing are contaminated with RSV-RNA and may have a role in transmission.